1981
DOI: 10.1161/01.str.12.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemic attacks associated with hypotension in hypertensive patients with carotid artery stenosis.

Abstract: SUMMARY In a group of 132 patients with transient ischemic attacks (TIAs) 7 patients (4 men, 3 women, ages 64 to 81) had TIAs preceded by hypotension. The average fall of mean blood pressure during an attack was 26.4 ± 5.5 mm Hg (SD). Only one of these patients had a TIA which was not preceded by hypotension. This episode occurred during a paroxysm of coughing. All 7 of these patients had hypertension, and cerebral arteriography performed in 4 of the 7 revealed hemodynamically significant carotid artery stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Although Torvik and Skullerud 12 did not find that cerebral infarction after cardiac arrest was correlated with the location and degree of cerebral atherosclerosis, hypertensive patients with ca- rotid artery stenosis may be more susceptible to focal cerebral ischemia in the presence of acute hypotension. 14 There is a tendency for cerebral infarction, associated with systemic hypotension, to occur in a distal field distribution, 15 but this pattern was not observed in our patients. In one study, 16 16 of 208 patients with ischemic cerebral infarction (7.7%) had hypotension at the onset of symptoms, often because of antihypertensive therapy.…”
Section: Discussioncontrasting
confidence: 50%
“…Although Torvik and Skullerud 12 did not find that cerebral infarction after cardiac arrest was correlated with the location and degree of cerebral atherosclerosis, hypertensive patients with ca- rotid artery stenosis may be more susceptible to focal cerebral ischemia in the presence of acute hypotension. 14 There is a tendency for cerebral infarction, associated with systemic hypotension, to occur in a distal field distribution, 15 but this pattern was not observed in our patients. In one study, 16 16 of 208 patients with ischemic cerebral infarction (7.7%) had hypotension at the onset of symptoms, often because of antihypertensive therapy.…”
Section: Discussioncontrasting
confidence: 50%
“…tFrom an independently measured supine ankle-arm blood pressure measurement a series of 132 patients admitted for evaluation of TTAs and observed with serial BP measurements, 20% had documented hypotensive episodes (decrease in mean BP of 20 mm Hg or greater within 4 hours), associated with either antihypertensive therapy, cerebral arteriography, or postural changes. 4 In another series of 80 consecutive patients seen within 2 weeks of a TIA, 16% were found to have OH, and in 9% an OH-concurrent TIA was observed. 3 These clinical studies do not suggest a higher rate of OH among TIA patients than is found in the CHS cohort overall.…”
Section: Discussionmentioning
confidence: 93%
“…Jackson et al 14 reported six hypertensive patients who were admitted to the hospital in a coma following rapid reduction of blood pressure to normotensive values; one had residual deficit. Ruff et al 15 noted, in a study of 132 patients with transient ischemic attacks, that in 7 patients the ischemic attacks occurred during hypotension; all 7 had hypertension, and 4 of these 7 had significant carotid stenosis. Rosenfeld et al 16 noted in 208 consecutive ischemic strokes that 16 could be attributed totally or partially to hypotension, usually iatrogenic; 12 of these 16 patients were known to be hypertensive prior to the strokes.…”
Section: Discussionmentioning
confidence: 99%